Amar Dan Nahi Serta Sighat Taklif Dalam Kaidah Tafsir - Sari Madani Rambe; Alwizar (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
The purpose of this article is to comprehensively explore the rules of amar and nahi and sighat taklif in the rules of interpretation. This research uses a qualitative methodology, emphasizing the field of library studies, with the aim of understanding the rules of amar and nahi and sighat taklif in the rules of interpretation. This research reveals that the various interpretations put forward by our scholars who are only human have something to do with what they must follow, the question of interpreting the Koran is very diverse with the various methods available in interpreting the Koran. With the knowledge of the Qur'an that has been discovered by previous scholars, we just need to develop the method. One of the methods that will be discussed in this research is the rules of exegesis related to amar and nahi and sighat taklif in the Al-Qur'an and the application of the text and its context in the reality of life.